From Casual Talk to Academic Discourse: Students’ Adaptation to Formal Speaking in Academic Settings - Ruly Morgana; Hanna Qoulan Syadidah; Farisa Ade Fiola (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines students’ Linguistic adaptation when shifting from casual communication to formal academic speaking in academic settings. Using a descriptive qualitative case study approach, data were collected through semi-structured interviews, observation, and documentation. The findings show that language adaptation occurs gradually as students adjust personal communication habits to academic discourse norms. Internal factors such as self-awareness, speaking anxiety, and vocabulary mastery, along with external factors including social environment, academic exposure, and teacher support, influence this process. The study contributes to sociolinguistic understanding and highlights the importance of developing formal speaking skills higher education.